Intelligent Systems for Modelling of a Tubular Conveyor for Collection and Sorting Solid Waste - Bulatov, Nurzhan (Journal of Environmental Accounting and Management, 2026)
In today's world, there is the need to solve the growing problem of waste management and increase environmental sustainability in urban conditions, where today more than half of the world's population lives in cities. The aim of the work is to develop the concept and technical implementation of a tubular conveyor designed for automated waste collection and sorting in multi-storey residential buildings and to analyse its effectiveness and environmental value. The study developed a tubular conveyor system for collecting and sorting waste in multi-storey residential buildings. The technical project included the creation of an efficient infrastructure, including transport routes, marshalling yards, and system management software. Modelling of the system operation process allowed optimising its performance and resource consumption. The results of the study confirmed that the use of a tubular conveyor greatly simplifies the collection, transportation, and sorting of waste in multi-storey residential buildings. The practical value of the study is to create more efficient and sustainable waste management systems in urban multi-storey residential complexes, which contributes to reducing the environmental burden and improving the quality of urban life.